2017
DOI: 10.1002/jso.24654
|View full text |Cite
|
Sign up to set email alerts
|

Surgical strategies and novel therapies for locally advanced pancreatic cancer

Abstract: Many patients with pancreatic cancer are not candidates for surgical resection due to involvement of critical mesenteric vascular structures. We compare and contrast the commonly used classification systems for borderline resectable and locally advanced pancreatic cancer. We describe the current strategies in managing venous and arterial involvement, as well as the role of neoadjuvant chemotherapy and chemoradiation, before explanding on a novel clinical trial in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…However, more recent studies from high‐volume centers have demonstrated similar outcomes between patients undergoing venous resection and reconstruction and patients with more easily resectable tumors 60,61 . An MD Anderson study of 141 patients concluded that vein reconstruction (VR) did not alter median survival rates (23.4 months vs. 26.5 months without VR) suggesting that venous involvement was more a function of the vein as a bystander than aggressive underlying biology 62,63 . These findings highlight the importance of patient selection and of the experience needed to perform these procedures, both of which lead to better outcomes.…”
Section: Surgical Therapymentioning
confidence: 93%
See 1 more Smart Citation
“…However, more recent studies from high‐volume centers have demonstrated similar outcomes between patients undergoing venous resection and reconstruction and patients with more easily resectable tumors 60,61 . An MD Anderson study of 141 patients concluded that vein reconstruction (VR) did not alter median survival rates (23.4 months vs. 26.5 months without VR) suggesting that venous involvement was more a function of the vein as a bystander than aggressive underlying biology 62,63 . These findings highlight the importance of patient selection and of the experience needed to perform these procedures, both of which lead to better outcomes.…”
Section: Surgical Therapymentioning
confidence: 93%
“…This makes the SMA margin, also known as the uncinate or retroperitoneal margin, the most commonly positive margin during a pancreatectomy 64 . Most studies investigating the feasibility and benefit of arterial resection and reconstruction (ARR) in LAPC are small and difficult to generalize 63 . A 2011 meta‐analysis including 26 studies and 2243 patients found an increase in the rates of perioperative mortality and poor long‐term outcomes (decreased survival at 1 and 3 years) in patients undergoing ARR compared with patients who did not undergo ARR (OR 5.04; p < .0001).…”
Section: Surgical Therapymentioning
confidence: 99%
“…[ 57 ] A chemotherapy up-front approach has already become the gold standard for borderline-resectable, or locally-advanced pancreas cancers. [ 59 ] Indeed, patients with tumours considered unresectable may become resectable in 10%–20% of cases with an upfront treatment strategy with chemotherapy with or without radiation. [ 59 ] At the 2018 American Society of Clinical Oncology meeting a prospective randomized controlled trial comparing chemotherapy and radiation prior to surgery, to upfront surgery for resectable pancreas cancer demonstrated improvement in median overall survival, time until PC recurrence, and the chance of surviving longer than 2 years was higher with preoperative treatment.…”
Section: Should Neoadjuvant Therapy Be Applied To All Patients With Pmentioning
confidence: 99%
“…These factors promote a high risk of neoplastic invasion of these vascular structures (6)(7)(8)(9) . Resection of vascular structures adjacent to the organ, even in cases of extensive invasion, has been practiced in recent years, but its perioperative outcomes are still poorly understood in our context, in addition to its impact on overall and disease-free survival (10)(11)(12) .…”
Section: Pancreaticoduodenectomy With Venous Resection: An Analysis Omentioning
confidence: 99%